Identificación de insectos que se encuentran en los corredores biológicos alternando con el cultivo de hortalizas agroecológicas en el campus Salache, Latacunga, Cotopaxi 2022-2023. - Alquinga Escobar, Yesenia Nicole (2023)
In the present investigation, it was carried out at the Technical University of Cotopaxi in order to conserve insect-plant biodiversity. The research focuses on the problem of excessive and inappropriate use of agrochemicals that damage the environment, causing contamination of the soil, air and water, altering the ecosystem, threatening flora and fauna. Furthermore, its irresponsible use increases production costs and accelerates pest resistance. The objectives of the study are to identify biological insects in corridors alternated with vegetables, such as Lavender (Lavandula lanata), Dill (Anethum graveolens) and Ruda (Ruta graveolens) in order to know, attract, house and conserve the biodiversity of insects and compare their effect with the growth of vegetables such as lettuce (Lactuca sativa L.), beetroot (Beta vulgaris) and chard (Beta vulgaris L. var cicla L.). The collection was carried out with an entomological net, one pass on each side of the corridor, every 15, 30, 45 and 60 days, this due to the flowering stage for its subsequent identification under a digital microscope and the help of entomological keys to know which family they belong to, data was also taken to demonstrate the growth and development of the vegetables. The results highlight the effectiveness of biological corridors in the case of lavender and rue, because there was a better response in growth and development of vegetables, dill serves as a mechanism for attracting beneficial insects, but due to the height of the plant caused nutrient deficiency that was the main cause of growth disturbances, however, more study and monitoring is needed to fully understand its long-term impact and optimize its use in sustainable agriculture.